609 Metachronous Osteoid Osteoma of the Mid-Diaphysis of the Fibula and Distal Humerus: A Case Report. (19th August 2022) - Adlan, A; Azzopardi, C; Davies, AM; Botchu, R
Abstract: A 7-year-old boy presented with a 4-week history of pain and swelling of the right leg. He had a history of mucoepidermoid carcinoma of the parotid gland, treated by surgical resection without any complication. There was no other significant past medical history. A radiograph of the right leg showed a lytic lesion of the right diaphysis of the fibula with periosteal reaction. An MRI of the right leg showed osteoid osteoma of the fibula with marked cortical thickening with osseous and soft tissue oedema. The patient subsequently had a Jamshidi biopsy and curettage of the lesion, with the histopathological results of the biopsy showing fragments of a typical osteoid osteoma nidus with irregular calcified bony lamellae. His symptoms had significantly improved after the procedure, and he was ambulating without any discomfort or pain. The patient remained asymptomatic until he returned seven years later with right elbow swelling, pain and reduced range of movement over 2–3 months. A radiograph of the elbow joint had shown a large effusion with a sclerotic lesion on the coronoid fossa of the distal humerus in keeping with an osteoid osteoma. The patient had a confirmational biopsy and subsequently radiofrequency ablation of the lesion with complete resolution of pain. To our knowledge, our case is an atypical presentation of osteoid osteoma in two widely separate bones, between the lower and the upper limb separated by seven years disease-free interval.